Physician Labor Supply, Financial Incentives, and Access to Healthcare - Lionel Wilner; Philippe Choné (CESifo GmbH, 2025)
To empirically assess how physicians respond to financial incentives, we leverage a quasi-natural experiment in France where most GPs' fees are regulated. In 2017, a wide-scale regulatory change caused the price of a visit to increase from exteuro23 to exteuro25. Relying on granular claims data covering the universe of patients, doctors, and visits, we show that physician activity grew by nearly 9% after the price increase, yielding a unitary price elasticity of healthcare provision. The number of distinct patients examined increased substantially, while the provision of medical services per patient hardly changed, resulting in a slight increase in physicians' number of days worked. Drug prescription per patient is also shown to decrease, suggesting that the policy was cost-effective and enhanced access to healthcare, with limited adverse effects. Early-career physicians responded strongly to these financial incentives, while later-career physicians hardly changed their labor supply behavior.
Keywords: I11; I18; J44; 330; physician labor supply; financial incentives; claims data; access to healthcare; medical spending